Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jmv.24771
|View full text |Cite
|
Sign up to set email alerts
|

A novel preservative‐free seasonal influenza vaccine safety and immune response study in the frame of preclinical research

Abstract: The paper describes the results of preclinical testing of the preparation "Vaccine allantoic split-virus inactivated against seasonal influenza." Acute toxicity and local irritating effect, anaphylactic reactions to different antigens (vaccine and ovalbumin), delayed-type hypersensitivity to ram erythrocytes, humoral immune response in hemaggtination reaction, immunogenic activity was studied in laboratory animals of various species (mice, rats, guinea pigs). Comparative analysis of the results from testing im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…17,18 Adhering the principles of ITPIV project aimed at extension of available vaccine production, reduction in number of steps, and appropriate analytical trials the researchers of the RIBSP developed a preservative-and adjuvant-free vaccine against seasonal influenza. 19,14 One of solid arguments in favor of adjuvant-free vaccine is recommendation of annual immunization because of short duration of immune protection after single vaccination. 20 | 47…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…17,18 Adhering the principles of ITPIV project aimed at extension of available vaccine production, reduction in number of steps, and appropriate analytical trials the researchers of the RIBSP developed a preservative-and adjuvant-free vaccine against seasonal influenza. 19,14 One of solid arguments in favor of adjuvant-free vaccine is recommendation of annual immunization because of short duration of immune protection after single vaccination. 20 | 47…”
Section: Role Of the Funding Sourcementioning
confidence: 99%
“…[11][12][13] To ensure seasonal influenza prophylaxis in the Republic of Kazakhstan the Research Institute for Biological Safety Problems has developed a seasonal influenza split vaccine that is available for manufacturing as well as reliable for safety and immunogenicity. 14…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 The previous preclinical and phase I clinical trials of RIBSP vaccine showed excellent results in comparison with the split vaccine VAXIGRIP Ò . 10,11 The phase I clinical study of the vaccine in healthy subjects below 50 years of age showed good safe profile. Humoral immune response to the vaccine met three requirements of the European Committee to human influenza vaccines (CPMP/ EWP/214/96).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 This vaccine is easily manufactured and was shown to be safe and highly immunogenic. [9][10][11] Application of RIBSP vaccine without adjuvants and preservatives makes it different from commercially available vaccines. We believe that the components of annually applied influenza vaccines (aluminium hydroxide, thiomersal etc.)…”
Section: Introductionmentioning
confidence: 99%